Yolk sac tumor in sigmoid colon with liver metastasis: A rare case report - Muddasetty, Rohith; Mahadevappa, Basant; Pai, Vishwajeeth; Jeevan, H R (Indian Journal of Case Reports, 2024)
Extragonadal germ cell tumor (EGGCT) is a rare tumor of primordial germ cells. They commonly involve the central nervous system and anterior mediastinum. The gastrointestinal system is a rare site for EGGCTs. Here, we present the case of a 34-year-old lady who presented with bleeding per rectum. She was evaluated with colonoscopy which showed a growth in the sigmoid colon and biopsy suggestive of poorly differentiated adenocarcinoma. Further evaluation showed multiple liver metastases. Considering colorectal liver metastasis, she was treated with liver-directed neoadjuvant chemotherapy. Following four cycles of chemotherapy, she underwent anterior resection of the sigmoid colon and microwave ablation of the liver metastasis. The final histopathological examination changed the diagnosis as yolk sac tumor. She is currently receiving chemotherapy. Proper small biopsy evaluation with immunohistochemical staining especially when it was a poorly differentiated adenocarcinoma would have prompted us for an appropriate neoadjuvant therapy to improve patient outcome.